Cancer in infancy: Experience of Children Welfare Teaching Hospital, Medical City Complex, Baghdad - Al-Maimory, Samaher T.; Al-Darraji, Amir F.; Al-saeed, Raghad M.; Al-Hadad, Salma (Journal of the Faculty of Medicine Baghdad, 2015)
Background: It is becoming increasingly apparent that the study of infant cancer may lead to further understanding of the mechanisms of carcinogenesis, due to the unique clinical, genetic, and epidemiologic characteristics of cancer in infant.Objectives: To study the clinical and pathological presentation of infants with cancer, their outcome and survival.Patients & methods: A retrospective study was done over a 6 years period between (Jan.1st.2001- Dec. 31st. 2006), reviewed the records of 85 infants diagnosed and treated in oncology unit, children welfare teaching hospital, medical city-Baghdad.Results: The majority of patients 57(67%) were from Baghdad & surrounding provinces; Leukemia was the most common type of cancer reported in 26(30.5%) infants followed by Neuroblastoma in 25(29.4%) infants. Males were more common than females with a ratio of 1.5:1 with duration of onset more than one month in 60(72.3%) patients. Pallor & fever were the most common presenting symptoms in 56(65.8%) and 43(50.5%) patients respectively. Bone marrow was the most common site of involvement in 31(36.4%) patients. Event free survival in treated patients was 16.4% with high rates of death (32.9%) and patients lost to follow-up were 24(28.2%).Conclusions: The study showed low event free survival due to high mortality rate due to lack of adequate supportive care, intensive care unit, bone marrow transplant facility and abandonment of treatment.